2020
DOI: 10.1186/s12903-020-01137-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of information and communication technologies in Latin American dentists: a cross-sectional study from Ecuador

Abstract: Background: The use of information and communication technologies (ICTs) provide the tools for enabling fast and reliable real-time communications, as well as the transfer of information between dental professionals and their patients. However, little is known about the frequency and preference of ICTs among Latin-American dentists. Our study aims to fill this gap by assessing different aspects related to ICTs, mainly the frequency of use, perceptions, and barriers among Ecuadorian dentists. Methods: An anonym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One study on US dental educators reported that older dental educators favored SM use [ 32 ]. On the other hand, two studies reported that younger dentists favored SM more than older dentists [ 30 , 39 ]. A possible explanation for having older participants in our study favor SM’s use would be that most of them are consultants and specialists who have been trained in the US and Europe and have private practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study on US dental educators reported that older dental educators favored SM use [ 32 ]. On the other hand, two studies reported that younger dentists favored SM more than older dentists [ 30 , 39 ]. A possible explanation for having older participants in our study favor SM’s use would be that most of them are consultants and specialists who have been trained in the US and Europe and have private practices.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is not similar to some other reported studies. For example, one study conducted in Ecuador reported that dentists with more than eight years of experience were associated with a lower likelihood of using SM [ 39 ]. Furthermore, it has been reported that there was no association between years of experience and SM use among sampled dentists in one study in South Africa [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to competently utilize technology equipment and tools is perceived to be a crucial skill that may improve employability, as well as professional performance and survival 26 . In dentistry, technology is used in multiple facets, including management, education, provision of treatment, and communication among colleagues, patients, and the public 27 . The conduction of OPL prepares UG and PG students with such skills, which can be further enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…26 In dentistry, technology is used in multiple facets, including management, education, provision of treatment, and communication among colleagues, patients, and the public. 27 The conduction of OPL prepares UG and PG students with such skills, which can be further enhanced. Support for the use and subscription of technology-based tools, as well the provision of related training indicates positive implications for further development in the conduction of online-related activities, including OPL.…”
Section: Knowledge Recall and Informationseekingmentioning
confidence: 99%
“…The use of information and communication technologies, digital health [154], is creating opportunities in Ecuador to support care practices in clinical and non-clinical settings [21,24,80,125]. In clinical settings, digital health is facilitating the monitoring of vital signs [40], digitalization of medical records [56], communication and interaction between clinicians and with patients (e.g., What-sApp) [22,25], localization of medical areas and doctor's offices [143], and medical training and tele-consultations [147]. In nonclinical settings, mobile phones, apps, SMS, e-mail, online resources and social media (e.g., WhatsApp, YouTube, Facebook) are facilitating care after hospitalization [88] and self-care management of a variety of chronic conditions such as diabetes [92], hypertension [24], chronic kidney disease [21], asthma [23], and cancer [108] by receiving, looking and sharing information between patients and health staff.…”
Section: Digital Health In the Ecuadorian Contextmentioning
confidence: 99%